Perception of Digital Storytelling in Overcoming Fear for Speaking English through Interdisciplinary Project of Gender Issues - Puspita Dewi; Dian Eka Sari (Institut Agama Islam Negeri Palopo, 2022)
Learning speaking has many challenging, particularly for students who have obstacles speaking in public places. This study reports on a project designed by the students to evaluate the development of their speaking skill through the digital storytelling with mobile devices. This study explores the perception of the learners on the digital storytelling in learning speaking and how the digital storytelling effects on students’ speaking. This research involved English students for Department of English Literature in the second semester who took speaking subject. A qualitative research was used in this study adapted a workshop approach and RASE (Resources, Activity, Support, and Evaluation) with three phases pre-production, production, and post-production and supported by a quantitative data by filling a questionnaire. The research results show that digital storytelling has positive impact to students because they believe that it encouraged them to learn writing, grammar, pronunciation, writing, and reading with the highest percentage of the students’ response is 55.6%. The learners also agree that the project can support them to be more confident and familiar with social phenomena involving women issues. This research is expected to contribute to the teaching and learning second or foreign language.